Pengembangan media pembelajaran berbasis simulasi lalu lintas sebagai pengenalan gerakan salat dalam pembelajaran PAI - Nisa', Khoirun (Maliki Interdisciplinary Journal, 2025)
This study aims to develop a non-digital instructional media based on traffic simulation integrated with prayer movements to enhance students' understanding of Islamic prayer practices in Islamic Religious Education (PAI) classes. The research employed a Research and Development (R&D) approach using the ADDIE model, consisting of five stages: Analysis, Design, Development, Implementation, and Evaluation. The media developed includes a game board, toy cars, traffic signs representing prayer movements, and instruction cards used in an educational game. The results show that this media effectively increases students’ learning interest, understanding of prayer movements, and active engagement in the learning process. Furthermore, it strengthens religious values such as discipline and obedience. The evaluation reveals that while there are visual aspects that need improvement, this media is feasible to be further developed as a contextual and enjoyable learning tool for young learners.